Analisis Kemampuan Berpikir Kritis Peserta Didik dalam Memecahkan Masalah Matematis Ditinjau dari Mathematical Belief - Jannah, Ellysa Ummirotul; Fathani, Abdul Halim; Fuady, Anies (Jurnal Pendidikan Matematika, 2022)
This study aims to determine the level of students' critical thinking skills in solving mathematical problems discussed from mathematical beliefs. The approach used in this study is a qualitative approach with a descriptive type of research. This research was carried out at MTs Roudlotul Muta'abbidin Payaman, Lamongan. The selection of subjects in this study was carried out by purposive sampling method, namely the selection with certain considerations. The research subjects were selected based on the high, medium, and low levels of mathematical belief as seen from the results of the questionnaire. The instruments used in this study were a mathematical confidence questionnaire, critical thinking skills test questions, and interview guidelines. The results of this study indicate that: 1) Students with mathematical confidence have very good critical thinking skills, namely meeting the indicators of interpretation, analysis, evaluation, and inference, 2) students with moderate mathematical belief categories have good enough critical thinking skills, namely meeting indicators of interpretation, analysis, and evaluation, and 3) students with low mathematical confidence categories have the ability to think critically, namely meeting the evaluation and inference indicators.